Conceptual model of azerbaijani language ecosystem in the electronic government - Ramiz Aliguliyev; Farhad Yusifov; Rasim, Aliguliyev (Universidad Pablo de Olavide, 2025)
The digital age, characterized by the development of technology and benefits of the Internet, threatens the preservation of linguistic diversity. Technological revolutions, disasters, pandemics, wars and rapid changes in the demographic situation in the world lead to the destruction of language ecosystems and the disappearance of language diversity. In this regard, protection of language diversity has become one of the urgent issues in the rapidly globalizing world under the influence of information technologies. Therefore, safeguarding the Azerbaijani language and expanding language services on the e-government platform are crucial concerns.This study aims to analyze the challenges and opportunities for integrating the Azerbaijani language into e-government platforms in the context of digitalization and globalizationMethodology.The article examines approaches, views and initiatives related to the impact of globalization on the linguistic-cultural space and language processes.